Strategi Pengembangan Bisnis Makanan Ikan: Kasus Waralaba “Ngikan Yuk” di Rawamangun Jakarta Timur - Eleanor, Angelica Elizabeth; Afriansyah, Afriansyah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Nowadays, with many culinary businesses scattered in various places, the business competition between each existing culinary business is getting tighter and each other is trying to get the attention of consumers. Various culinary businesses are currently growing using their respective strategies which have led to a culinary business getting bigger and having franchises in various places. On the other hand, there are also culinary businesses that are even more losing money because they cannot compete with other culinary businesses. Not only that, there are culinary businesses that only sell well at the beginning and are quiet until they close a few moments later. However, there are also culinary businesses that sell well in the beginning and continue to survive for a long period of time. These various possibilities can be influenced by their respective business development strategies, particularly marketing and sales patterns.